Normativity-Deductivity of Ibn Rusyd’s Bidâyah Al-Mujtahid Wa Nihâyah Al-Muqtashi - Abdul Aziz, Jamal (KARSA Journal of Social and Islamic Culture, 2016)
Ibn Rusyd, Â better known as Â Moslem philosopher, but he was actuallyÂ Â an expert in other fields, among which was islamic jurisprudence (fiqh).Â He wrote a monumental work in the field of Islamic jurisprudence, namely the BidÃ¢yah al-Mujtahid wa NihÃ¢yah al-Muqtashid. This book compiles the book systematically, logical, and comprehensive, and serves a variety of opinions from various schools of jurisprudence that developed at that time objectively. This paper examines about Muqaddimah BidÃ¢yah Kitab al-Mujtahid that comprise theories of understanding religious text (al-adillah al-sharâ€™Ã®yah) underlying causes of dissent which will be described in it, also on the systematization of this book. I finally concludes that the book BidÃ¢yah al-Mujtahid wa NihÃ¢yah al-Muqtashid is fiqh comparison described systematically-logical-argumentative and contains themes of fiqh holistically-comprehensive. Copyright (c) 2016 by KARSA. All right reservedÂ DOI: 10.19105/karsa.v24i1.1000